Liquid metal composite conductive adhesive as well as preparation method and application thereof

By using liquid metal composite conductive adhesive, the existing transparent LED glass displays have solved the problems of poor conductivity, uneven brightness, large heat generation and high cost, and high conductive materials with high conductivity, high thermal conductivity and low cost, which have improved the stability and application range of the display.

CN119552615APending Publication Date: 2025-03-04YUNNAN KEWEI LIQUID METAL VALLEY R & D CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411617514.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing transparent LED glass display screens have poor conductivity due to the surface resistance of the ITO conductive layer, uneven brightness, large heat generation, high cost, and thin thickness of the conductive plating layer, wide line and poor adhesion, which affects stability.

Method used

A liquid metal composite conductive glue is provided, which consists of 60-90 wt% conductive filler and 10-40 wt% resin matrix. The conductive filler includes liquid metal, copper powder impregnated by liquid metal, irregular low-melting point metal powder particles, sheet or linear or spherical silver powder, silver-clad copper powder, carbon nanotubes, etc. Through proper grinding and homogenization, the adhesion ability and conductivity of the conductive material to the substrate are improved.

Benefits of technology

It realizes a liquid metal composite conductive adhesive material with low cost, high conductivity and high thermal conductivity, improves the adhesion ability and conductivity stability of the conductive material and the substrate, expands the application range, and reduces the cost of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of LED display screen new materials, in particular to a liquid metal composite conductive adhesive and a preparation method and application thereof. The liquid metal composite conductive adhesive comprises a conductive filler and a resin matrix in a mass ratio of (60-90): (10-40), wherein the conductive filler comprises at least two of liquid metal, copper powder infiltrated by the liquid metal, irregular low-melting-point metal powder particles, flaky or linear or sphere-like silver powder, silver-coated copper powder and carbon nanotubes. The composite conductive adhesive suitable for the transparent LED display screen developed by the invention is excellent in performance, is suitable for wide electronic and electrical application fields, and has great market prospects in the aspects of improving the conductive stability, reducing the cost and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials for LED display screens, and in particular to a liquid metal composite conductive adhesive and a preparation method and application thereof. Background Art

[0002] With the continuous updating and development of LED display technology, various types of flexible or rigid transparent LED smart displays have emerged on the market. For example, flexible transparent substrate LED displays and rigid transparent glass LED displays are becoming more and more widely used in life due to their transparent characteristics, beautiful appearance and strong adaptability to various installation and use environments.

[0003] Existing transparent LED glass display screens mainly use magnetron sputtering ITO powder to form a conductive layer, or form a metal conductive coating by chemical plating, high-temperature spraying of copper, chromium, nickel, titanium, molybdenum and other metals, and then form an LED conductive path through laser etching or other methods. The LED lamp is then installed on the conductive path by welding or bonding to finally achieve a conductive connection.

[0004] Taking the rigid transparent LED glass display screen treated with ITO film as an example, the surface resistance of the ITO conductive layer causes a voltage drop in the conductive area far away from the power output end, resulting in poor conductivity, which leads to uneven LED brightness and affects the visual effect; not only that, the surface resistance generates a large amount of heat, which increases the power loss and makes the use cost high. At the same time, if the generated heat is not dissipated in time, it will also induce various potential dangers, such as cracking or breaking of glass due to uneven hot and cold during use. In addition, the transparent glass treated with ITO film has high cost and limited use scenarios, and cannot be widely promoted and applied. Similarly, the conductive layer is formed on the transparent glass by chemical plating and spraying. Although the cost is reduced compared with the ITO conductive film, these conductive coatings are thin in thickness, wide in line, and have poor adhesion to the substrate, which seriously affects the stability. Invention patent application CN 115458516A discloses "a liquid metal LED display screen and its preparation method and application", but does not further elaborate on its printing process and its preparation process, and the liquid metal LED display screen prepared by it is a whole module, which is difficult to repair and difficult to ensure later maintenance and use. Invention patent application CN 117050686 A discloses "low temperature curing conductive adhesive and its preparation method and transparent display screen", but it can only achieve low temperature curing, its application range is relatively narrow, and there are certain difficulties in technical and market promotion. At present, it is urgent to provide a new type of liquid metal composite conductive adhesive and its preparation and application. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a liquid metal composite conductive adhesive and a preparation method and application thereof.

[0006] The present invention aims to solve the problems of high cost, high heat generation, poor adhesion, unstable conductivity, etc. of transparent rigid or flexible conductive screens prepared by existing ITO conductive films, chemical plating films, spray films, etc., and provides a liquid metal composite conductive adhesive for transparent display screens and its preparation and application methods, which can effectively solve the above problems and provide a liquid metal composite conductive adhesive material with low cost, high conductivity and high thermal conductivity. At the same time, the adhesion ability and conductive stability of the conductive material to the substrate can be further improved by cooperating with a suitable coating and printing process. The present invention also greatly improves the scope of application and application scenarios of the liquid metal composite conductive adhesive, and has great market value. The present invention provides a liquid metal composite conductive adhesive composition with excellent performance, a preparation method of the liquid metal composite conductive adhesive, and an application method of the liquid metal composite conductive adhesive.

[0007] Specifically, the first aspect of the present invention provides a liquid metal composite conductive adhesive, the components of which include a conductive filler and a resin matrix in a mass ratio of 60-90:10-40; wherein the conductive filler includes at least two of liquid metal, copper powder soaked in liquid metal, irregular low-melting-point metal powder particles, flaky or linear or quasi-spherical silver powder, silver-coated copper powder, and carbon nanotubes. The composite conductive adhesive developed by the present invention for transparent LED display screens has excellent performance, is suitable for a wide range of electronic and electrical applications, and has great market prospects in terms of improving conductive stability and reducing costs.

[0008] Preferably, the liquid metal composite conductive adhesive is composed of 60.0wt%-90.0wt% of conductive filler and 10.0wt%-40.0wt% of resin matrix; preferably, the liquid metal composite conductive adhesive is composed of 70.0wt%-85.0wt% of conductive filler and 15.0wt%-30.0wt% of resin matrix. For example, the conductive filler is 74.5wt%, 75.0wt%, 75.5wt%, 76.5wt%, 80.0wt%, etc. and any value therebetween. By adopting the liquid metal composite conductive adhesive with a resin matrix of the preferred ratio, it performs well in terms of conductivity, mechanical properties, adhesion, thermal stability, etc., and is suitable for a wide range of electronic and electrical applications, while having a lower cost advantage.

[0009] Further preferably, the conductive filler includes a first conductive filler and a second conductive filler; the first conductive filler is one or more of liquid metal, copper powder soaked in liquid metal, irregular low melting point metal powder particles, silver-coated copper powder, and carbon nanotubes; the second conductive filler is flaky, linear, or spherical silver powder; Preferably, the mass ratio of the first conductive filler to the second conductive filler is 5.0-50.0:20.0-75.0, preferably 40-45:32.5-40, and more preferably 42.0-42.5:32.5-35.

[0010] More preferably, the liquid metal and the liquid metal that soaks the copper powder are composed of gallium and gallium-based single or multiple alloys, and the particle size of the copper powder soaked in the liquid metal is preferably 0.1-3.0 μm.

[0011] Further preferably, the irregular low melting point metal powder particles are composed of one or more of gallium-based, indium-based, tin-based, bismuth-based single or multiple alloys, and the particle size is preferably 0.5-5.0 μm.

[0012] More preferably, the flaky, linear or quasi-spherical silver powder has a particle size of 0.5-10.0 μm.

[0013] More preferably, the particle size of the silver-coated copper powder or carbon nanotube is 0.1-3.0 μm.

[0014] Preferably, the resin matrix is ​​thermosetting or light-curing.

[0015] As a preferred embodiment of the thermosetting resin matrix of the present invention, the thermosetting resin matrix includes the following components: epoxy resin, curing agent, diluent, toughening agent and coupling agent.

[0016] Preferably, the mass ratio of the epoxy resin, the curing agent, the diluent, the toughening agent and the coupling agent is 15-90:1-10:1-10:0-5:0.1-3.

[0017] More preferably, the mass ratio of the epoxy resin, curing agent, diluent, toughening agent and coupling agent is 15-22:1.3-3.5:1.0-2.7:0-5:0.2-3, preferably 15.5-20.6:1.85-2.95:1.55-2.15:0-0.75:0.34-0.6. For example, the ratios may be 19.5:2.95:1.95:0:0.6, 15.5:1.86:1.55:0.75:0.34, 20:2.85:1.55:0.5:0.6, 20.5:1.95:1.95:0:0.6, 20.6:1.85:2.05:0:05, 15.5:1.85:2.15:0:0.5, and the like. In addition, any combination of the ratios within the above ranges is also acceptable.

[0018] More preferably, the epoxy resin is selected from one or more of E51 epoxy resin, HS170 epoxy resin, silicone-modified 3201 epoxy resin, and EP-4000 epoxy resin.

[0019] More preferably, the curing agent is selected from one or more of triethanolamine, diethylenetriamine, menthanediamine, p-phenylenediamine, boroalkyl tertiary amine, dicyandiamide, polyamide, 2-ethyl-4-methylimidazole, methyl nadic anhydride, diethylenetriamine and butyl glycidyl ether.

[0020] Further preferably, the diluent is selected from one or more of diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dimethyl adipate, dimethyl glutarate, diethylene glycol butyl ether, ethylene glycol diglycidyl ether, and C12-14 alkyl glycidyl ether.

[0021] More preferably, the toughening agent is selected from one or more of 4-aminobenzoic acid ester, liquid nitrile rubber, liquid polybutadiene rubber, and butyl phthalate.

[0022] More preferably, the coupling agent is selected from one or more of KH550, KH560, and KH570.

[0023] As a preferred embodiment of the photocurable resin matrix of the present invention, the photocurable resin matrix includes the following components: a photosensitive high molecular polymer, a photoinitiator, a reactive diluent, a coupling agent, an antioxidant and a toughening agent.

[0024] The mass ratio of the photocurable photosensitive high molecular polymer, the photoinitiator, the active diluent, the coupling agent, the antioxidant and the toughening agent is 15-90:1-10:10-30:0-5:0.1-3:0-5.

[0025] In the photocurable resin matrix, the photosensitive high molecular polymer includes one or more of epoxy acrylate resin, polyurethane acrylate, polyether acrylate, and acrylate-modified polysiloxane; and / or, the photoinitiator includes one or more of benzil derivatives, N,N-dimethylbenzylamine, triphenylphosphine, chromium acetylacetonate, and tetraethylammonium bromide; and / or, the active diluent includes one or more of 1,4-cyclohexanedimethanol methacrylate, trimethylolpropane triglycidyl ether, and dodecanol acrylate; and / or, the coupling agent includes one or more of KH560, KH570, and KH792; and / or, the antioxidant includes one or two of p-hydroxyanisole and distearyl thiodipropionate; and / or, the toughening agent includes one or two of epoxy fatty acid butyl ester and isooctyl acrylate.

[0026] The second aspect of the present invention provides a method for preparing the liquid metal composite conductive adhesive, comprising the following steps: b) Preliminary mixing: the resin matrix and the conductive filler are mixed and stirred. Preferably, the stirring device is further sealed and evacuated for stirring.

[0027] c) Grinding: The primary mixed sample is subjected to three-roll grinding, preferably, the primary mixed sample is subjected to three-roll grinding in a stepwise decreasing manner.

[0028] d) Homogenization: Vacuum the ground conductive adhesive and homogenize it.

[0029] and optionally, e) sealing and storing the homogenized liquid metal composite conductive adhesive under low temperature conditions.

[0030] Preferably, in the conductive filler of step b), the liquid metal accounts for 0-5.0wt% and the flaky silver powder accounts for 40.0wt%-70.0wt%.

[0031] In a preferred embodiment of the present invention, the preparation method comprises the following steps: a) Weighing: According to the specific ratio of the liquid metal composite conductive adhesive, accurately weigh the resin matrix and the conductive filler restored to room temperature.

[0032] b) Preliminary mixing: Set the stirring parameters, add the resin matrix into the planetary mixer for stirring, and then gradually add the conductive filler. The conductive filler needs to be added and stirred at the same time until all the conductive filler is added. Further, the planetary mixer is sealed and vacuumed for stirring to complete the preliminary mixing, and the preliminary mixing of the conductive glue is completed.

[0033] c) Grinding: After the planetary mixer is finished, take out the premixed sample and perform three-roll grinding to remove the conductive filler agglomeration. Set the grinding speed parameters, the gap parameters between the inlet and outlet rollers, perform three-roll grinding on the premixed sample in a step-by-step manner, and determine the final roller parameters with reference to the powder particle size D50. This completes the conductive glue grinding process.

[0034] d) Homogenization: The conductive adhesive after three-roll grinding is transferred to a homogenizer, and the parameters of homogenization rotation, revolution and rotation time are set. The ground conductive adhesive is vacuumed and homogenized to remove bubbles in the conductive adhesive and make the composition uniform, thus completing the conductive adhesive homogenization process.

[0035] e) The prepared liquid metal composite conductive adhesive is sealed and stored at a low temperature of -35°C.

[0036] Further preferably, the preparation method of the liquid metal composite conductive adhesive further comprises the preparation of a resin matrix: B) Mechanical stirring: The various components of the resin matrix are mixed and stirred.

[0037] C) Homogenization: Vacuum the sample after mechanical stirring for homogenization and degassing.

[0038] D) Storage: Store the homogenized resin matrix in a sealed container at low temperature.

[0039] The third aspect of the present invention provides the use of the liquid metal composite conductive adhesive in a transparent LED display screen, preferably in screen printing, steel screen printing or glue dispensing by a glue dispenser.

[0040] Preferably, it is applied to screen or steel screen printing: by screen or steel screen printing, the liquid metal composite conductive adhesive is used to print conductive circuits on a transparent rigid or flexible substrate to provide conductive connection circuits or electrodes for a transparent LED display screen; more preferably, the liquid metal composite conductive adhesive is taken out and returned to room temperature, then coated on a prefabricated screen or steel mesh for transfer printing, and then the liquid metal composite conductive adhesive is transferred to a transparent rigid or flexible substrate; for the thermosetting resin substrate, the substrate printed with the liquid metal composite conductive adhesive is placed in an oven device, the liquid metal composite conductive adhesive is heated and cured, and the cured liquid metal composite conductive adhesive is used to achieve conductive connection; for the photocurable resin substrate, the substrate printed with the liquid metal composite conductive adhesive is placed under ultraviolet light of a fixed wavelength for photocuring, and the cured liquid metal composite conductive adhesive is used to achieve conductive connection.

[0041] Preferably, it is applied to dispensing by a dispensing machine: the liquid metal composite conductive adhesive is dispensed by a dispensing machine, and is used for conductive connection between an LED lamp and a transparent rigid or flexible substrate printed with a conductive circuit to obtain a transparent LED lamp display screen; more preferably, a rigid or flexible substrate with a conductive circuit obtained by screen printing or steel screen printing is used as a substrate for preparing a transparent LED display screen, or other transparent rigid or flexible conductive substrates preferably include transparent conductive glass coated with ITO; preferably, the liquid metal composite conductive adhesive is taken out from a freezing device, warmed to room temperature and installed on a dispensing machine, and the transparent rigid or flexible conductive substrate is subjected to dispensing treatment at the position where the LED lamp is installed; the LED lamp is mounted at the dispensing position, and the mounted components of the LED lamp are cured by light curing or heat curing, and the cured conductive adhesive is used to achieve conductive connection.

[0042] In a further preferred embodiment, the method for using the liquid metal composite conductive adhesive comprises: 1) Screen printing: Through screen printing, conductive circuits can be printed on transparent rigid or flexible substrates to provide conductive connection circuits or electrodes for transparent LED displays.

[0043] The conductive glue is taken out of the freezer and returned to room temperature, and then coated on a prefabricated screen for screen transfer. After the operation, the conductive glue will be transferred to a transparent rigid or flexible substrate. Further, the substrate printed with the conductive glue is placed in an oven or ultraviolet light device, and the temperature or light wavelength and time parameters are set to heat or light-cure the conductive glue. The cured conductive glue can achieve conductive connection.

[0044] 2) Stencil printing: Through the steel screen printing method, conductive circuits can be printed on transparent rigid or flexible substrates to provide conductive connection circuits for transparent LED displays.

[0045] The conductive glue is taken out from the freezer and returned to room temperature, and then coated on a prefabricated steel mesh for steel mesh printing. After the operation, the conductive glue will be transferred to a transparent rigid or flexible substrate. Further, the substrate printed with the conductive glue is placed in an oven or ultraviolet light device, and the temperature or light wavelength and time parameters are set to heat or light-cure the conductive glue. The cured conductive glue can achieve conductive connection.

[0046] 3) Dispensing machine dispensing: The liquid metal composite conductive adhesive can be directly dispensed using a dispensing machine, and can be used for conductive connection between LED lamps and transparent rigid or flexible substrates printed with conductive circuits to make transparent LED lamp display screens. Furthermore, the rigid or flexible substrate with conductive circuits obtained by screen printing or steel screen printing can be used as a substrate for preparing LED transparent display screens, and transparent rigid or flexible conductive substrates prepared by other processes, such as ITO-coated transparent conductive glass, can also be used.

[0047] Take out the conductive glue from the freezer and return it to room temperature, then install it on the glue dispenser, and perform glue dispensing on the transparent rigid or flexible conductive substrate where the LED light needs to be installed according to the program setting. Furthermore, after completing the glue dispensing process, the LED light mounting process is then performed at the corresponding glue dispensing position; then the transparent rigid or flexible conductive substrate with the LED light installed is placed in an oven or ultraviolet light device, and the temperature or light wavelength and time parameters are set to heat or light-cure the conductive glue, and the cured conductive glue can achieve conductive connection.

[0048] The beneficial effects of the present invention are at least: 1. The present invention provides a liquid metal composite conductive adhesive for transparent display screens and a preparation and application method thereof, which can provide a liquid metal composite conductive adhesive material with low cost, high conductivity and high thermal conductivity. At the same time, the adhesion ability and conductive stability of the conductive material to the substrate can be further improved by cooperating with a suitable coating and printing process.

[0049] 2. The liquid metal composite conductive adhesive of the present invention has excellent mechanical properties after curing, high conductivity, and a wide range of applications. The present invention can be used for a long or short period of time according to the application scenario and corresponding use requirements, and the resin matrix and the liquid metal composite material are used in a suitable ratio.

[0050] 3. Compared with traditional silver paste printing materials, the liquid metal composite conductive adhesive of the present invention has lower cost and wider application range under the same performance conditions. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products or can be prepared by known methods. If no specific techniques or conditions are specified in the examples, they are all conventional methods or the techniques or conditions described in the literature in this field, or according to the product instructions. If the manufacturers of the reagents and instruments are not specified, they are all conventional products that can be purchased through regular channels.

[0053] Example 1 The present embodiment relates to a thermosetting liquid metal composite conductive adhesive for conductive connection lines on a transparent glass display screen and a preparation and application method thereof, which includes three parts: the composition of the liquid metal composite conductive adhesive, the preparation method of the liquid metal composite conductive adhesive, and the application method of the liquid metal composite conductive adhesive.

[0054] The composition ratio of the thermosetting liquid metal composite conductive adhesive is shown in the following table: Table 1

[0055] The preparation method of the thermosetting liquid metal composite conductive adhesive comprises the following steps: 1. Resin matrix preparation (1) Weighing: First, accurately weigh E51 epoxy resin, triethanolamine, diethylene glycol butyl ether, and KH560 according to the ratio; (2) Mechanical stirring: Add the weighed components into the mixer in turn for mechanical stirring, set the stirring speed to 800 rpm / min, and stir for a total of 10 minutes; (3) Homogenization: Transfer the sample after mechanical stirring to a homogenizer and evacuate it for homogenization and degassing. Set the homogenizer rotation speed to 600 rpm / min and the revolution speed to 1300 rpm / min. Homogenize for 3 minutes at a negative pressure of 75 MPa. After homogenization, a resin matrix is ​​finally obtained; (4) Storage: Store the resin matrix in a -35°C low-temperature freezer and keep it sealed.

[0056] 2. Conductive adhesive preparation (1) Weighing: According to the specific ratio of the thermosetting liquid metal composite conductive adhesive, accurately weigh the resin matrix prepared in the first step and restored to room temperature, the copper powder impregnated with Ga with a particle size distribution of 1-2μm, and the flaky silver powder conductive filler with a particle size distribution between 1.0-7.0μm. (2) Preliminary mixing: Set the stirring speed of the planetary mixer to 15Hz, add the resin matrix into the planetary mixer for stirring, and then gradually add the copper powder impregnated with Ga and the flaky silver powder. During the powder addition process, it is necessary to stir while adding until all the powders are added. The conductive filler should be added to the resin matrix according to the following principles, that is, the filler addition requires that the silver powder with large particles be added first and then the small particles, and the spherical powder be added first and then the flaky powder be added in batches. Further, the planetary mixer is sealed and evacuated to -75MPa for stirring to complete the preliminary mixing. (3) Grinding: After the planetary mixer is finished, take out the initial mixed sample and perform three-roll grinding to remove the conductive filler agglomeration and make the prepared conductive adhesive more uniform. Set the grinding speed to 100 rpm / min, adjust the gap parameters between the inlet and outlet rollers, and perform three-roll grinding on the initial mixed sample in a step-by-step manner as follows to complete the conductive adhesive grinding process; The gap between the inlet rollers is 140 μm and the outlet roller gap is 100 μm as the first grinding; The gap between the inlet rollers is 100 μm and the gap between the outlet rollers is 70 μm for the second grinding; The third grinding is performed with a gap of 80 μm between the inlet rollers and 50 μm between the outlet rollers; The fourth grinding is performed with a gap of 50 μm between the inlet rollers and 30 μm between the outlet rollers; The fifth grinding is performed with a gap of 30 μm between the inlet rollers and 15 μm between the outlet rollers; The sixth grinding was performed with a gap of 20 μm between the inlet rollers and 10 μm between the outlet rollers.

[0057] (4) Homogenization: Transfer the conductive adhesive after three-roll grinding to a homogenizer. Set the homogenizer rotation speed to 600 rpm / min, the revolution speed to 1200 rpm / min, homogenize for 1 minute, and the negative pressure to 75 MPa to remove bubbles in the prepared conductive adhesive and make its composition uniform. This completes the conductive adhesive homogenization process.

[0058] 3. Storage: Store the finished conductive adhesive in a -35℃ low-temperature freezer and keep it sealed.

[0059] The application method of the thermosetting liquid metal composite conductive adhesive adopts screen printing. Through the screen printing method, conductive circuits can be printed on a transparent glass substrate to provide conductive connection circuits or electrodes for the transparent glass LED display.

[0060] First, take out the conductive glue prepared in the second step from the freezer and return it to room temperature; then apply it to the prefabricated screen for screen transfer, and transfer the conductive glue to the transparent glass substrate. After this operation, the conductive glue is transferred to the transparent glass substrate. Further, put the transparent glass substrate printed with the conductive glue into an oven, set the baking temperature to 120°C and the baking time to 3 hours, heat and cure the conductive glue, and the cured conductive glue can achieve conductive connection.

[0061] Example 2 The present embodiment relates to a thermosetting liquid metal composite conductive adhesive for conductive bonding of LED lights on a transparent ITO conductive glass display screen and its preparation and application method, which includes three parts: the composition of the liquid metal composite conductive adhesive, the preparation method of the liquid metal composite conductive adhesive, and the application method of the liquid metal composite conductive adhesive.

[0062] The composition ratio of the thermosetting liquid metal composite conductive adhesive is shown in the following table: Table 2

[0063] The preparation method of the thermosetting liquid metal composite conductive adhesive comprises the following steps: 1. Resin matrix preparation (1) Weighing: First, accurately weigh the silicone-modified 3201 epoxy resin, boron alkyl tertiary amine, diethylene glycol butyl ether, 4-aminobenzoate, and KH560 according to the ratio; (2) Mechanical stirring: Add the weighed components into the mixer in turn for mechanical stirring, set the stirring speed to 1000 rpm / min, and stir for a total of 5 minutes; (3) Homogenization: Transfer the sample after mechanical stirring to a homogenizer and evacuate it for homogenization and degassing. Set the homogenizer rotation speed to 700 rpm / min and the revolution speed to 1400 rpm / min. Homogenize for 3 minutes at a negative pressure of 75 MPa. After homogenization, a resin matrix is ​​finally obtained; (4) Storage: Store the resin matrix in a -35°C low-temperature freezer and seal it for storage.

[0064] 2. Preparation of conductive adhesive.

[0065] (1) Weighing: According to the specific ratio of the liquid metal composite conductive adhesive, accurately weigh the resin matrix prepared in the first step and restored to room temperature, the copper powder with a particle size of 1-3 μm infiltrated by the GaInSn alloy, and the flaky silver powder conductive filler with a particle size distribution between 1.0-10.0 μm; (2) Preliminary mixing: Set the stirring speed of the planetary mixer to 15 Hz, add the resin matrix into the planetary mixer for stirring, and then gradually add the GaInSn alloy and flaky silver powder. During the process of adding the GaInSn alloy and flaky silver powder, it is necessary to stir while adding until all are added. Further, the planetary mixer is sealed and evacuated to -75 MPa for stirring to complete the preliminary mixing; (3) Grinding: After the planetary mixer is stirred, take out the preliminarily mixed sample for three-roll grinding to remove the conductive filler agglomeration and make the prepared conductive adhesive more uniform. The grinding speed is set to 100 rpm / min, the gap parameters between the inlet and outlet rollers are adjusted, and the primary mixed sample is subjected to three-roll grinding in a step-by-step decreasing manner as follows to complete the conductive adhesive grinding process; The gap between the inlet rollers is 120 μm and the outlet roller gap is 90 μm for the first grinding; The gap between the inlet rollers is 80 μm and the outlet roller gap is 50 μm for the second grinding; The third grinding is performed with a gap of 40 μm between the inlet rollers and 20 μm between the outlet rollers; The fourth grinding was performed with a gap of 20 μm between the inlet rollers and 10 μm between the outlet rollers.

[0066] (4) Homogenization: Transfer the conductive adhesive after three-roll grinding to a homogenizer. Set the homogenizer rotation speed to 500 rpm / min, the revolution speed to 1000 rpm / min, and the homogenization for 2 minutes. The negative pressure is 75 MPa to remove bubbles in the prepared conductive adhesive and make its composition uniform. This completes the conductive adhesive homogenization process.

[0067] 3. Storage: Store the finished conductive adhesive in a -35℃ low-temperature freezer and keep it sealed.

[0068] Among them, the application method of the thermosetting liquid metal composite conductive adhesive adopts the dispensing method of a dispensing machine, taking out the conductive adhesive from the freezer, returning it to room temperature, and then installing it on the dispensing machine, and dispensing the transparent ITO conductive glass at the position where the LED lamp needs to be installed according to the program setting. Furthermore, after completing the dispensing process, the LED lamp mounting process is then carried out at the corresponding dispensing position; then the transparent ITO conductive glass with the LED lamp installed is placed in an oven device, the temperature is set to 160°C and the time is 3 hours, and the conductive adhesive is heated and cured. The cured conductive adhesive can realize the conductive connection between the ITO film and the LED lamp.

[0069] Example 3 The present embodiment relates to a thermosetting liquid metal composite conductive adhesive for conductive connection lines on a transparent flexible LED display screen and a preparation and application method thereof, which includes three parts: the composition of the liquid metal composite conductive adhesive, the preparation method of the liquid metal composite conductive adhesive, and the application method of the liquid metal composite conductive adhesive.

[0070] The composition ratio of the thermosetting liquid metal composite conductive adhesive is shown in the following table: Table 3

[0071] The preparation method of the thermosetting liquid metal composite conductive adhesive comprises the following steps: 1. Resin matrix preparation (1) Weighing: First, accurately weigh the silicone-modified 3201 epoxy resin, triethanolamine, diethylene glycol butyl ether, liquid nitrile rubber, and KH570 according to the ratio; (2) Mechanical stirring: Add the weighed components into the mixer in turn for mechanical stirring, set the stirring speed to 900 rpm / min, and stir for a total of 10 minutes; (3) Homogenization: Transfer the sample after mechanical stirring to a homogenizer and evacuate it for homogenization and degassing. Set the homogenizer rotation speed to 500 rpm / min and the revolution speed to 1000 rpm / min. Homogenize for 1.5 minutes at a negative pressure of 75 MPa. After homogenization, a resin matrix is ​​finally obtained; (4) Storage: Store the resin matrix in a -35°C low-temperature freezer and keep it sealed.

[0072] 2. Preparation of conductive adhesive.

[0073] (1) Weighing: According to the specific ratio of the thermosetting liquid metal composite conductive adhesive, accurately weigh the resin matrix prepared in the first step after returning to room temperature, and the In with a particle size distribution between 0.5-5.0 μm.52 Sn 48 alloy and a flaky silver powder conductive filler with a particle size distribution between 1.0 and 6.0 μm; (2) initial mixing: setting the stirring speed of the planetary mixer to 15 Hz, adding the resin matrix into the planetary mixer for stirring, and then gradually adding In 52 Sn 48 Alloy and flake silver powder, in In 52 Sn 48 The alloy and flaky silver powder need to be added while stirring until all are added. Further, the planetary mixer is sealed and evacuated to -75MPa for stirring to complete the initial mixing; (3) Grinding: After the planetary mixer is completed, take out the initial mixed sample and perform three-roll grinding to remove the conductive filler agglomeration and make the prepared conductive adhesive more uniform. Set the grinding speed to 120 rpm / min, adjust the gap parameters between the inlet and outlet rollers, and perform three-roll grinding on the initial mixed sample in a step-by-step decreasing manner as follows to complete the conductive adhesive grinding process; The gap between the inlet rollers is 120 μm and the outlet roller gap is 90 μm for the first grinding; The gap between the inlet rollers is 90 μm and the outlet roller gap is 60 μm for the second grinding; The third grinding is performed with a gap of 60 μm between the inlet and outlet rollers and a gap of 30 μm; The fourth grinding is performed with a gap of 30 μm between the inlet rollers and 20 μm between the outlet rollers; The fifth grinding was performed with a gap of 20 μm between the inlet rollers and 10 μm between the outlet rollers.

[0074] (4) Homogenization: Transfer the conductive adhesive after three-roll grinding to a homogenizer. Set the homogenizer rotation speed to 600 rpm / min, the revolution speed to 1200 rpm / min, homogenize for 1 minute, and the negative pressure to 75 MPa to remove bubbles in the prepared conductive adhesive and make its composition uniform. This completes the conductive adhesive homogenization process.

[0075] 3. Storage: Store the finished conductive adhesive in a -35℃ low-temperature freezer and keep it sealed.

[0076] Among them, the application method of the thermosetting liquid metal composite conductive adhesive adopts a steel screen printing method to print a conductive circuit on a flexible substrate screen. First, take out the conductive adhesive prepared in the second step from the freezer and return it to room temperature; then apply it to the prefabricated steel mesh for steel screen transfer, and transfer the conductive adhesive to the transparent flexible substrate screen. After this operation, the conductive adhesive is transferred to the transparent flexible substrate screen. Furthermore, the transparent flexible substrate screen printed with the conductive adhesive is placed in an oven device, the baking temperature is set to 90°C and the baking time is set to 5h, and the conductive adhesive is heated and cured. The cured conductive adhesive can achieve conductive connection of the flexible screen.

[0077] Example 4 The present embodiment relates to a thermosetting liquid metal composite conductive adhesive for conductive connection lines on a transparent glass display screen and a preparation and application method thereof, which includes three parts: the composition of the liquid metal composite conductive adhesive, the preparation method of the liquid metal composite conductive adhesive, and the application method of the liquid metal composite conductive adhesive.

[0078] The composition ratio of the liquid metal composite conductive adhesive is shown in the following table: Table 4

[0079] The preparation method of the thermosetting liquid metal composite conductive adhesive and the application method of the thermosetting liquid metal composite conductive adhesive are the same as those in Example 1 and will not be described in detail herein. The difference is that the liquid metal composite conductive adhesive is set to have a baking temperature of 160° C. and a baking time of 2 hours, so that the composite conductive adhesive can be cured to achieve conductive connection.

[0080] Example 5 The present embodiment relates to a thermosetting liquid metal composite conductive adhesive for conductive connection lines on a transparent flexible LED display screen and a preparation and application method thereof, which includes three parts: the composition of the liquid metal composite conductive adhesive, the preparation method of the liquid metal composite conductive adhesive, and the application method of the liquid metal composite conductive adhesive.

[0081] The composition ratio of the liquid metal composite conductive adhesive is shown in the following table: Table 5

[0082] The preparation method of the thermosetting liquid metal composite conductive adhesive and the application method of the thermosetting liquid metal composite conductive adhesive are the same as those in Example 3 and will not be described in detail here. The difference is that the liquid metal composite conductive adhesive is set to a baking temperature of 160°C and a baking time of 2.5 hours, so that the composite conductive adhesive can be cured to achieve conductive connection.

[0083] Example 6 The present embodiment relates to a thermosetting liquid metal composite conductive adhesive for conductive bonding of LED lights on a transparent ITO conductive glass display screen and its preparation and application method, which includes three parts: the composition of the liquid metal composite conductive adhesive, the preparation method of the liquid metal composite conductive adhesive, and the application method of the liquid metal composite conductive adhesive.

[0084] The composition ratio of the liquid metal composite conductive adhesive is shown in the following table: Table 6

[0085] The preparation method of the thermosetting liquid metal composite conductive adhesive and the application method of the thermosetting liquid metal composite conductive adhesive are the same as those in Example 2 and will not be described in detail herein. The difference is that the liquid metal composite conductive adhesive is set to have a baking temperature of 160° C. and a baking time of 2.5 h, so that the composite conductive adhesive can be cured to achieve conductive connection.

[0086] Example 7 The present embodiment relates to a photocurable liquid metal composite conductive adhesive for conductive connection lines on a transparent flexible LED display screen and its preparation and application method, which includes three parts: the composition of the liquid metal composite conductive adhesive, the preparation method of the liquid metal composite conductive adhesive, and the application method of the liquid metal composite conductive adhesive.

[0087] The composition ratio of the light-curing liquid metal composite conductive adhesive is shown in the following table: Table 7

[0088] The preparation method of the light-curing liquid metal composite conductive adhesive comprises the following steps: 1. Resin matrix preparation (1) Weighing: First, accurately weigh polyurethane acrylate, triphenylphosphine, dodecanol acrylate, and KH570 reagent according to the ratio; (2) Mechanical stirring and mixing: Add the weighed components into the mixer in turn for mechanical stirring, set the stirring speed to 900 rpm / min, the stirring temperature to 60°C, and stir for a total of 45 minutes; (3) Storage: Take out the prepared resin matrix, fill it, refrigerate it, and store it in a sealed manner away from light.

[0089] 2. Preparation of conductive adhesive.

[0090] (1) Weighing: According to the specific ratio of the liquid metal composite conductive adhesive, accurately weigh the above resin matrix, Sn42Bi58 alloy with a particle size distribution between 0.5-5.0μm and flaky silver powder conductive filler with a particle size distribution between 1.0-7.0μm; (2) Preliminary mixing: Set the stirring speed of the planetary mixer to 15Hz, add the resin matrix into the planetary mixer for stirring, and then gradually add Sn42Bi58 alloy and flaky silver powder. During the process of adding Sn42Bi58 alloy and flaky silver powder, it is necessary to stir while adding until all are added. Further, the planetary mixer is sealed and evacuated to -75MPa for stirring to complete the preliminary mixing; (3) Grinding: After the planetary mixer is stirred, take out the preliminarily mixed sample for three-roll grinding to remove the conductive filler agglomeration and make the prepared conductive adhesive more uniform. The grinding speed is set to 150 rpm / min, the gap parameters between the inlet and outlet rollers are adjusted, and the mixed sample is subjected to three-roll grinding in a step-by-step manner as follows to complete the conductive adhesive grinding process; The gap between the inlet rollers is 140 μm and the outlet roller gap is 110 μm for the first grinding; The gap between the inlet rollers is 110 μm and the outlet roller gap is 80 μm for the second grinding; The third grinding is performed with a gap of 80 μm between the inlet rollers and 50 μm between the outlet rollers; The fourth grinding is performed with a gap of 50 μm between the inlet rollers and 30 μm between the outlet rollers; The fifth grinding is performed with a gap of 30 μm between the inlet rollers and 20 μm between the outlet rollers; The sixth grinding was performed with a gap of 20 μm between the inlet rollers and 10 μm between the outlet rollers.

[0091] (4) Homogenization: Transfer the conductive adhesive after three-roll grinding to a homogenizer. Set the homogenizer rotation speed to 600 rpm / min, the revolution speed to 1200 rpm / min, homogenize for 1 minute, and the negative pressure to 75 MPa to remove bubbles in the prepared conductive adhesive and make its composition uniform. This completes the conductive adhesive homogenization process.

[0092] 3. Storage: Take out the finished conductive glue, fill it and keep it away from light, and store it in a sealed container in a refrigerator.

[0093] The method for applying the light-curing liquid metal composite conductive adhesive adopts screen printing. Through screen printing, conductive circuits can be printed on a transparent glass substrate to provide conductive connection circuits or electrodes for the transparent glass LED display.

[0094] First, take out the conductive glue prepared in the second step from the freezer and return it to room temperature; then apply it on the prefabricated screen for screen transfer, and transfer the conductive glue to the transparent glass substrate. After this operation, the conductive glue is transferred to the transparent glass substrate. Further, the transparent glass substrate printed with the conductive glue is placed in a photocuring device, and the wavelength is set to 360nm ultraviolet light, and the conductive glue is irradiated at an intensity of 75 mw / cm for 60s to perform photocuring treatment, and the cured conductive glue can achieve conductive connection.

[0095] Example 8 This embodiment relates to a light-curing liquid metal composite conductive adhesive for conducting LED lights on a transparent ITO conductive glass display screen and its preparation and application method, including three parts: liquid metal composite conductive adhesive composition, liquid metal composite conductive adhesive preparation method, liquid metal composite conductive adhesive application method. The composition of the light-curing liquid metal composite conductive adhesive is shown in the following table: The preparation method of the light-curing liquid metal composite conductive adhesive comprises the following steps: 1. Resin matrix preparation (1) Weighing: First, accurately weigh bisphenol A epoxy acrylate, chromium acetylacetonate, trimethylolpropane triglycidyl ether, and KH560 reagent according to the ratio; (2) Mechanical stirring and mixing: Add the weighed components into the blender in turn for mechanical stirring, set the stirring speed to 800 rpm / min, the stirring temperature to 70°C, and stir for a total of 30 minutes; (3) Storage: Take out the prepared resin matrix, fill it, refrigerate it, and store it in a sealed manner away from light.

[0096] 2. Preparation of conductive adhesive.

[0097] (1) Weighing: According to the specific ratio of the liquid metal composite conductive adhesive, accurately weigh the above resin matrix, the Ga particles are distributed in the range of 0.5-2 μm. 80 In 20 Alloy liquid microspheres, Ga 80 In 20Alloy-impregnated copper powder, and flaky silver powder conductive filler with a particle size distribution between 1.0-7.0μm; (2) Preliminary mixing: Set the stirring speed of the planetary mixer to 15Hz, add the resin matrix into the planetary mixer for stirring, and then gradually add the copper powder and flaky silver powder impregnated with the Ga80In20 alloy. During the powder addition process, it is necessary to add and stir at the same time until all the powders are added. Further, the planetary mixer is sealed and evacuated to -75MPa for stirring to complete the preliminary mixing; (3) Grinding: After the planetary mixer is completed, take out the preliminary mixed sample for three-roll grinding to remove the conductive filler agglomeration and make the prepared conductive adhesive more uniform. Set the grinding speed to 100 rpm / min, adjust the gap parameters between the inlet and outlet rollers, and perform three-roll grinding on the outlet mixed sample in a step-by-step manner as follows to complete the conductive adhesive grinding process; The gap between the inlet rollers is 140 μm and the outlet roller gap is 100 μm as the first grinding; The gap between the inlet rollers is 100 μm and the outlet roller gap is 60 μm for the second grinding; The third grinding is performed with a gap of 60 μm between the inlet and outlet rollers and a gap of 30 μm; The fourth grinding was performed with a gap of 30 μm between the inlet rollers and 10 μm between the outlet rollers.

[0098] (4) Homogenization: Transfer the conductive adhesive after three-roll grinding to a homogenizer. Set the homogenizer rotation speed to 600 rpm / min, the revolution speed to 1200 rpm / min, homogenize for 1 minute, and the negative pressure to 75 MPa to remove bubbles in the prepared conductive adhesive and make its composition uniform. This completes the conductive adhesive homogenization process.

[0099] 3. Storage: Take out the finished conductive glue, fill it and keep it away from light, and store it in a sealed container in a refrigerator.

[0100] Among them, the application method of the photocurable liquid metal composite conductive adhesive is the dispensing method of the dispensing machine, taking out the conductive adhesive from the freezer, returning it to room temperature, and then installing it on the dispensing machine, and dispensing the transparent ITO conductive glass at the position where the LED lamp needs to be installed according to the program setting. Further, after completing the dispensing process, the LED lamp mounting process is then carried out at the corresponding dispensing position; then the transparent ITO conductive glass with the LED lamp installed is placed in the light curing equipment, the wavelength is set to 365nm ultraviolet light, and the conductive adhesive is irradiated at an intensity of 75 mw / cm for 60s to perform light curing treatment, and the cured conductive adhesive can achieve conductive connection.

[0101] Example 9 This embodiment relates to a light-curing liquid metal composite conductive adhesive for electrically connecting LED lights on a rigid display screen and its preparation and application method, including three parts: liquid metal composite conductive adhesive composition, liquid metal composite conductive adhesive preparation method, and liquid metal composite conductive adhesive application method. The composition ratio of the light-curing liquid metal composite conductive adhesive is shown in the following table: Table 9

[0102] The preparation method of the photocurable liquid metal composite conductive adhesive and the application method of the photocurable liquid metal composite conductive adhesive are the same as those in Example 8 and are not described in detail here. The difference is that the liquid metal composite conductive adhesive is photocured with ultraviolet light of 370 nm wavelength, and the conductive adhesive is photocured at an intensity of 65 mw / cm for 45 seconds, and the cured conductive adhesive can achieve conductive connection.

[0103] Example 10 This embodiment relates to a light-curing liquid metal composite conductive adhesive for electrically connecting LED lights on a rigid display screen and its preparation and application method, including three parts: liquid metal composite conductive adhesive composition, liquid metal composite conductive adhesive preparation method, and liquid metal composite conductive adhesive application method. The composition ratio of the light-curing liquid metal composite conductive adhesive is shown in the following table: Table 10

[0104] The preparation method of the photocurable liquid metal composite conductive adhesive and the application method of the photocurable liquid metal composite conductive adhesive are the same as those in Example 8 and are not described in detail here. The difference is that the liquid metal composite conductive adhesive is photocured with ultraviolet light of 360 nm wavelength, and the conductive adhesive is photocured at an intensity of 60 mw / cm for 90 seconds, and the cured conductive adhesive can achieve conductive connection.

[0105] Comparative Example 1 A heat-curing liquid metal composite conductive adhesive for conductive bonding of LED lamps on a transparent ITO conductive glass display screen, and a preparation and application method thereof, adopting the same method as Example 1, the only difference is that the mass proportion of the conductive filler is 91.00%, and the mass proportion of the resin matrix is ​​9.00%. The conductive adhesive prepared according to this ratio has too high viscosity, resulting in the inability to apply the adhesive, and the bonding strength drops sharply after thermal curing, which cannot meet the use requirements.

[0106] The following table shows the main physical property test results of Examples 1-10.

[0107] Table 11

[0108] The above embodiments show that the more silver powder there is, the better the conductivity is. Reasonable matching of conductive fillers can not only reduce costs, but also obtain better volume resistivity values. In addition, it can be seen that an increase in the proportion of conductive fillers in the liquid metal composite conductive adhesive will lead to a decrease in adhesion. The bonding strength is related to the content of the resin matrix. If the resin matrix content is not enough, the bonding strength is small and the bonding force is poor. However, too much resin matrix will result in a reduction in conductive fillers and a decrease in volume resistivity, and ultimately the conductive connection requirements cannot be met. Although the proportions and curing processes of Examples 1-10 are different, their volume resistivity and adhesion fully meet the use requirements of the transparent matrix screen, and the power-on test can obtain stable signal transmission and remain stable for a long time.

[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A liquid metal composite conductive adhesive, characterized in that: The components of the liquid metal composite conductive adhesive include a conductive filler and a resin matrix in a mass ratio of 60-90:10-40; wherein the conductive filler includes at least two of liquid metal, copper powder soaked in liquid metal, irregular low-melting-point metal powder particles, flaky or linear or spherical silver powder, silver-coated copper powder, and carbon nanotubes.

2. The liquid metal composite conductive adhesive according to claim 1, characterized in that: The liquid metal composite conductive adhesive consists of 60.0wt%-90.0wt% of conductive filler and 10.0wt%-40.0wt% of resin matrix; preferably, the liquid metal composite conductive adhesive consists of 70.0wt%-85.0wt% of conductive filler and 15.0wt%-30.0wt% of resin matrix.

3. The liquid metal composite conductive adhesive according to claim 2, characterized in that: The conductive filler comprises a first conductive filler and a second conductive filler; the first conductive filler is one or more of liquid metal, copper powder soaked in liquid metal, irregular low melting point metal powder particles, silver-coated copper powder, and carbon nanotubes; the second conductive filler is flaky, linear, or spherical silver powder; Preferably, the mass ratio of the first conductive filler to the second conductive filler is 5.0-50.0:20.0-75.

0.

4. The liquid metal composite conductive adhesive according to claim 3, characterized in that: The liquid metal and the liquid metal soaking the copper powder are composed of gallium and gallium-based single or multiple alloys, and the particle size of the copper powder soaked by the liquid metal is preferably 0.1-3.0 μm; And / or, the irregular low melting point metal powder particles are composed of one or more of gallium-based, indium-based, tin-based, bismuth-based single or multiple alloys, and the particle size is preferably 0.5-5.0 μm; And / or, the flaky, linear or quasi-spherical silver powder preferably has a particle size of 0.5-10.0 μm; And / or, the particle size of the silver-coated copper powder or carbon nanotube is 0.1-3.0 μm.

5. The liquid metal composite conductive adhesive according to any one of claims 1 to 4, characterized in that: The resin matrix is ​​a heat-curing type or a light-curing type; wherein the heat-curing type resin matrix comprises the following components: epoxy resin, curing agent, diluent, toughening agent and coupling agent; wherein the light-curing type resin matrix comprises the following components: photosensitive high molecular polymer, photoinitiator, active diluent, coupling agent, antioxidant and toughening agent. Preferably, the mass ratio of the thermosetting epoxy resin, curing agent, diluent, toughening agent and coupling agent is 15-90:1-10:1-10:0-5:0.1-3; the mass ratio of the light-curing photosensitive polymer, photoinitiator, active diluent, coupling agent, antioxidant and toughening agent is 15-90:1-10:10-30:0-5:0.1-3:0-5.

6. The liquid metal composite conductive adhesive according to claim 5, characterized in that: In the thermosetting resin matrix, the epoxy resin is selected from one or more of E51 epoxy resin, HS170 epoxy resin, silicone-modified 3201 epoxy resin, and EP-4000 epoxy resin; and / or, the curing agent is selected from one or more of triethanolamine, diethylenetriamine, menthane diamine, p-phenylenediamine, boroalkyl tertiary amine, dicyandiamide, polyamide, 2-ethyl-4-methylimidazole, methyl nadic anhydride, diethylenetriamine and butyl glycidyl ether; and / or, The diluent is selected from one or more of diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dimethyl adipate, dimethyl glutarate, diethylene glycol butyl ether, ethylene glycol diglycidyl ether, and carbon 12-14 alkyl glycidyl ether; and / or, the toughening agent is selected from one or more of 4-aminobenzoate, liquid nitrile rubber, liquid polybutadiene rubber, and butyl phthalate; and / or, the coupling agent is selected from one or more of KH550, KH560, and KH570; Preferably, in the photocurable resin matrix, the photosensitive high molecular polymer includes one or more of epoxy acrylate resin, polyurethane acrylate, polyether acrylate, and acrylate-modified polysiloxane; and / or, the photoinitiator includes one or more of benzil derivatives, N,N-dimethylbenzylamine, triphenylphosphine, chromium acetylacetonate, and tetraethylammonium bromide; and / or, the active diluent includes one or more of 1,4-cyclohexanedimethanol methacrylate, trimethylolpropane triglycidyl ether, and dodecanol acrylate; and / or, the coupling agent includes one or more of KH560, KH570, and KH792; and / or, the antioxidant includes one or both of p-hydroxyanisole and distearyl thiodipropionate; and / or, the toughening agent includes one or both of epoxy fatty acid butyl ester and isooctyl acrylate.

7. The method for preparing the liquid metal composite conductive adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: b) Preliminary mixing: mixing and stirring the resin matrix and the conductive filler. Preferably, the stirring device is further sealed and vacuumed for stirring; c) Grinding: Grinding the primary mixed sample by three rolls, preferably grinding the primary mixed sample by three rolls in a step-by-step decreasing manner; d) Homogenization: Vacuum the ground conductive adhesive and homogenize it.

8. The method for preparing the liquid metal composite conductive adhesive according to claim 7, characterized in that: It also includes the formulation of the resin matrix: B) Mechanical stirring: mixing and stirring the various components of the resin matrix; C) Homogenization: Vacuum the sample after mechanical stirring to perform homogenization and degassing treatment; D) Storage: Store the homogenized resin matrix in a sealed container at low temperature and away from light.

9. Use of the liquid metal composite conductive adhesive according to any one of claims 1 to 6 in a transparent LED display screen, preferably in screen printing, steel screen printing or dispensing by a dispensing machine.

10. The use according to claim 9, characterized in that: Application to screen or steel screen printing: by screen or steel screen printing, the liquid metal composite conductive adhesive is used to print conductive circuits on a transparent rigid or flexible substrate to provide conductive connection circuits or electrodes for a transparent LED display screen; preferably, the liquid metal composite conductive adhesive is taken out and returned to room temperature, then coated on a prefabricated screen or steel mesh for transfer printing, and then the liquid metal composite conductive adhesive is transferred to a transparent rigid or flexible substrate; for the thermosetting resin substrate, the substrate printed with the liquid metal composite conductive adhesive is placed in an oven device, the liquid metal composite conductive adhesive is heated and cured, and the cured liquid metal composite conductive adhesive is used to achieve conductive connection; for the photocurable resin substrate, the substrate printed with the liquid metal composite conductive adhesive is placed under ultraviolet light of a fixed wavelength for photocuring, and the cured liquid metal composite conductive adhesive is used to achieve conductive connection; Alternatively, the method is applied to dispensing by a dispensing machine: the liquid metal composite conductive adhesive is dispensed by a dispensing machine for conductive connection between an LED lamp and a transparent rigid or flexible substrate printed with a conductive circuit to obtain a transparent LED lamp display screen; preferably, a rigid or flexible substrate with a conductive circuit obtained by screen printing or steel screen printing is used as a substrate for preparing a transparent LED display screen, or other transparent rigid or flexible conductive substrates preferably include transparent conductive glass coated with ITO; preferably, the liquid metal composite conductive adhesive is taken out from a freezing device, warmed to room temperature and installed on a dispensing machine, and the transparent rigid or flexible conductive substrate is subjected to dispensing treatment at the position where the LED lamp is installed; the LED lamp is mounted at the dispensing position, and the mounted components of the LED lamp are cured by light curing or heat curing, and the cured conductive adhesive is used to achieve conductive connection.

Citation Information

Patent Citations

  • Liquid metal LED display screen and preparation method and application thereof

    CN115458516A

  • Low-temperature curing conductive adhesive, preparation method thereof and transparent display screen

    CN117050686A